Valoración del incremento de la proteína de Quinua Tunkahuan (chenopodium quinoa willd) en el proceso de Germinación. - Aimacaña Guamushig, Karina Liseth (2018)
The research was done at Latacunga canton, Eloy Alfaro Parish, Salache Bajo town, in the Technical University of Cotopaxi, Agroindustrial Engineering Career in coordination with the Andean Grain Research Project. The objective of the project was to evaluate the changes in the concentration of Quinua Tunkahuan protein (Chenopodium quinoa Willd) during the germination process, using the Kjeldhal method for the analysis of the proteins carried out in the LABOLAB laboratory, through the application of time and temperature variables, carrying out a chase in the different stages of the germinate process, developing germination on three occasions to obtain examples and evaluating in them the protein increase. A completely randomized factorial design (A* B) + 1 were applied with two replicas; where, factor A corresponds to temperature, factor B to time and control as the treatment that was not submitted to the germinate process, however, it was determined that the percentage of protein is capable of performing the respective interaction, making measurements in three different times (24 H - 48 H - 72 H) and two temperatures (20°C, 30°C) with the corresponding control treatment for each replica, according to each treatment in trays with a weight of 70g of Quinoa Tunkahuan seeds. The quantitative variable evaluated was: Protein (Kjeldahl Method) the microbiological variables studied were: mold and yeast count, E. coli, Staphylococcus aureus. The results obtained were evaluated by Tukey tests to determine the significance between the treatments and the control determining that statistically there is no significance but with the report of results obtained. It can be argued that there is a minimum increase in protein in the t2 treatments (15.83 %) and t5 (15.85) with respect to the protein percentage of the control (14.70%), with respect to the protein percentage of the control (14.70%), as it constitutes a viable alternative to improve the levels of protein malnutrition, since they stand out for their excellent nutritional value thus improving the product that can be elaborated from the Quinoa Tunkahuan flour germinated.